Pengembangan Media Flashcard Berbantuan Pixellab pada Materi Cerpen di Kelas XI Sekolah Menengah Atas Negeri 2 Lubuk Pakam - Nur Anisa; Nila Safina; Rika Kartika; Ali Ali; Rita Rita (Medan Resource Center, 2026)
The limited availability of innovative and technology-based learning media for short story instruction motivated the development of a Pixellab-assisted flashcard learning medium designed to support visually engaging and accessible learning experiences. This study aimed to develop, assess the feasibility of, and examine teacher and student responses toward the use of Pixellab-assisted flashcard learning media for short story learning materials among eleventh-grade students at State Senior High School 2 Lubuk Pakam. The population consisted of 394 students, with 36 students from Class XI-F selected as the sample. This study employed the Research and Development (R&D) method using Thiagarajan’s 4D model, which includes the stages of define, design, development, and dissemination. The results indicated that the developed product was feasible based on expert evaluations. Material Expert I assigned a score of 94% (Highly Feasible), while Material Expert II assigned 84% (Feasible). Design Expert I assigned 94% (Highly Feasible), and Design Expert II assigned 80% (Feasible). The teacher’s response indicated a score of 96% (Highly Feasible), while student responses reached 87.8% (Highly Effective). Data were also collected through teacher and student interviews. These findings suggest that the developed media is both feasible and effective, contributes pedagogically by enhancing student engagement in short story learning, and may serve as an alternative instructional resource in Indonesian language education.